(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
In the article, scientific proposals and practical recommendations were developed regarding the causes and solutions of some problems arising with the management of liquidity in commercial banks. In particular, relevant conclusions have been formed regarding the specific aspects of liquidity management in state commercial banks and private commercial banks.